Self-perception of dental appearance and awareness towards orthodontic treatment among undergraduate students and interns of dentistry - Acharya, Gaurav; Shrestha, Rosha; Shrestha, Parikshya; Ghimire, Luna (Journal of Chitwan Medical College, 2021)
Background: Patient’s perception of own facial appearance is also an important contributing factor for treatment planning. Also, knowledge and attitude of patients to orthodontic treatment is becoming more important in orthodontics these days. The study aimed to assess self-perception, awareness and attitude towards orthodontic treatment among dental students and interns. Methods: Data was collected through cross-sectional survey conducted among the dental students and dental interns in KIST Medical College through online google form. Study duration was from August 2021 - October 2021. The data was entered in SPSS software 20. Frequency distribution was generated for all variables. Categorical variables were evaluated using Chi-square test. Results: About 96.7% of the participants believe that orthodontic treatment will improve facial appearance. 61.5% believe that orthodontic treatment is a lengthy and painful procedure. 44.5% does not think orthodontic treatment weakens the teeth. 50% of female believe that orthodontic treatment will give the promising result. Statistically significant difference was obtained with respect to preference of different types of braces among students of different years. 54.9% of the participants are satisfied with the arrangements of their teeth, 20.9% had avoid smiling and 22.5% felt lack of confidence because of the appearance of their teeth. Almost half of the participants (50.5%) think they should have orthodontic treatment and 76.2% readily agree to orthodontic treatment if suggested by the dentist. Conclusions: Dental students and interns had a good knowledge about orthodontic treatment and positive attitude towards it. Gender difference exists regarding the awareness of orthodontic treatment. Statistically significant difference was found in preference of different types of braces in students of different years and interns.